2021
DOI: 10.1039/d1cp01058a
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the structures of sodiated β-cyclodextrin and its fragments

Abstract: We present cryogenic infrared spectra of sodiated β-cyclodextrin [β-CD+Na]+, a common cyclic oligosaccharide, and its main dissociation products upon collision-induced dissociation (CID). We characterize the parent ions using high-resolution ion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…25 Further insights have been provided by a study on Na + -tagged cyclodextrin by Carrascosa and co-workers. 26 It has recently been demonstrated that the structural information of oligosaccharides, including stereoisomerism, anomeric configuration, and linkage positions, can be obtained by the so-called logically derived sequence (LODES) tandem mass spectrometry (MS n ) approach. [27][28][29][30][31][32] To correctly interpret the MS results, it is helpful to understand the mechanisms of the different monosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…25 Further insights have been provided by a study on Na + -tagged cyclodextrin by Carrascosa and co-workers. 26 It has recently been demonstrated that the structural information of oligosaccharides, including stereoisomerism, anomeric configuration, and linkage positions, can be obtained by the so-called logically derived sequence (LODES) tandem mass spectrometry (MS n ) approach. [27][28][29][30][31][32] To correctly interpret the MS results, it is helpful to understand the mechanisms of the different monosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…MS/MS fragmentation studies were further employed to confirm the structures of CDCL main products. The fragmentation of CDCL derivatives proceeds similarly to other CD-oligoester derivatives [ 19 , 20 , 45 , 46 ], having two main pathways: the cleavage of the 1,4-glycosidic bond of β-CD [ 53 , 54 , 55 ] and the cleavage of the ester bonds from the CL attached to the β-CD molecule [ 56 , 57 , 58 ]. Oligocaprolactone fragmentation can occur either on the acyl side through 1-3 hydrogen rearrangements ( Scheme 2 A— a series ) or on the alkyl side through 1-4 hydrogen rearrangements of the ester bond ( Scheme 2 A— b series ).…”
Section: Resultsmentioning
confidence: 99%
“…For modified CDs, the fragmentation occurs via neutral losses of ( x *162 + y ) Da— y representing the molecular weight of the attached structures; in our particular case, y = n *114, which corresponded to the CL units ( Scheme 2 B). Deeper studies describing the mechanistic processes occurring during this type of cleavage may be found in recent reports [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its application in the field of carbohydrate research is steadily increasing for determining the connectivity and the configuration of saccharides [ 26 , 27 , 28 ]. However, for cyclodextrins, IM-MS is mainly described for the analysis of inclusion complexes and less often for their own characterisation [ 29 , 30 , 31 , 32 ]. As mentioned before, another fundamental aspect of ion mobility is that it gives access to the collision cross section (CCS) value, which, when compared to theoretical CCS values (CCS th ) obtained via molecular modelling techniques, allows for the validation of hypothetical structures.…”
Section: Resultsmentioning
confidence: 99%